2010
DOI: 10.1158/0008-5472.can-09-1887
|View full text |Cite
|
Sign up to set email alerts
|

GlcNAcylation Plays an Essential Role in Breast Cancer Metastasis

Abstract: GlcNAcylation, a dynamic posttranslational modification, is involved in a wide range of biological processes and some human diseases. Although there is emerging evidence that some tumor-associated proteins are modified by GlcNAcylation, the role of GlcNAcylation in tumor progression remains unclear. Here, we show that GlcNAcylation enhances the migration/invasion of breast cancer cells in vitro and lung metastasis in vivo. The decrease of cell surface E-cadherin is the molecular mechanism underlying GlcNAcylat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
222
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(235 citation statements)
references
References 36 publications
9
222
1
1
Order By: Relevance
“…The nucleocytoplasmic OGT (ncOGT) contains 13 TPRs, the mitochondrial OGT (mOGT) contains a mitochondrial-targeting sequence at its N-terminus and nine TPRs, and the shortest OGT isoform (sOGT) contains only two TPRs. Previous studies have indicated that the expression of OGT is increased in certain cancer types, but the OGT isoforms were not discriminated in these reports (11,12,14,22). Here, we detected by IB the expression of OGT using specific antibodies that recognize all three OGT isoforms, and the results showed that ncOGT and mOGT, but not sOGT, are detectable in all tested cell lines (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The nucleocytoplasmic OGT (ncOGT) contains 13 TPRs, the mitochondrial OGT (mOGT) contains a mitochondrial-targeting sequence at its N-terminus and nine TPRs, and the shortest OGT isoform (sOGT) contains only two TPRs. Previous studies have indicated that the expression of OGT is increased in certain cancer types, but the OGT isoforms were not discriminated in these reports (11,12,14,22). Here, we detected by IB the expression of OGT using specific antibodies that recognize all three OGT isoforms, and the results showed that ncOGT and mOGT, but not sOGT, are detectable in all tested cell lines (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…We previously reported that increased O-GlcNAcylation reduces the level of the cell surface protein E-cadherin, which has the potential to enhance cell invasion and metastasis in breast cancer cells (12). The binding of the E-cadherin/catenin complex to the cytoskeleton is essential for strong cell-cell adhesion (26), and we demonstrated that an increase in the O-GlcNAc level inhibits the formation of the E-cadherin/catenin/cytoskeleton complex (12).…”
Section: O-glcnac Inhibits the Formation Of The E-cadherin/cateninmentioning
confidence: 67%
See 1 more Smart Citation
“…EMT involves loss of epithelial markers such as E-cadherin and gain of mesenchymal markers such as vimentin and N-cadherin (79,81). We and others have found that reducing hyper-OGlcNAcylation in cancers increases expression of the epithelial marker E-cadherin and decreases expression of the mesenchymal marker vimentin, whereas elevating O-GlcNAc decreases expression of the epithelial marker E-cadherin in breast and liver cancer (8,15,78). The loss of E-cadherin is regarded as a key step in initiation of EMT (79), and transcription factors, including Snail, E47, and Zeb, can directly bind to the promoter of E-cadherin, thereby repressing its expression (82).…”
Section: O-glcnac and Cancer Cell Invasion And Metastasismentioning
confidence: 89%
“…Emerging evidence suggests that hyper-O-GlcNAcylation in cancers may be involved in tumor invasion and metastasis. Whereas increasing hyper-O-GlcNAcylation enhances the migration/invasion of breast and liver cancer cells, lowering hyper-O-GlcNAcylation by knockdown of OGT inhibits tumor invasion and metastasis in vivo and in vitro in breast and prostate cancer cells (7)(8)(9)78). The mechanisms by which hyper-O-GlcNAcylation may regulate tumor invasion and metastasis are only beginning to be understood.…”
Section: O-glcnac and Cancer Cell Invasion And Metastasismentioning
confidence: 99%